فعالية برنامج قائم على التعلم الموقفي في تنمية مهارات الفهم القرائي واللغة البراجماتية لدى تلاميذ المرحلة الابتدائية ذوي صعوبات القراءة - طلبة، أماني حامد مرغني (جامعة سوهاج - كلية التربية, 2022)
هدف البحث الحالي إلى تعرف فعالية برنامج قائم على التعلم الموقفي في تنمية مهارات الفهم القرائي واللغة البراجماتية لدى تلاميذ المرحلة الابتدائية ذوي صعوبات القراءة، وتكونت المجموعة التجريبية للبحث من (٣٠) تلميذا من تلاميذ الصف الرابع ذوي صعوبات القراءة، واشتملت مواد البحث وأدواته على: قائمة بمهارات الفهم القرائي، وقائمة بأبعاد اللغة البراجماتية، والبرنامج القائم على التعلم الموقفي، والذي اشتمل على: دليل المعلم، وكتاب التلميذ، واشتمل على أدوات القياس التالية: اختبار الفهم القرائي، ومقياس ملاحظة اللغة البراجماتية، تم استخدام المنهج التجريبي في اختيار مجموعة البحث وتطبيق البرنامج، واستخدام التصميم شبه التجريبي ذي المجموعة الواحدة من خلال التطبيقين القبلي والبعدي لأدوات البحث، وتم تطبيق البرنامج على التلاميذ مجموعة البحث، وتطبيق أدوات القياس عليهم قبليا وبعديا، وأظهرت النتائج تحسن التلاميذ في مهارات الفهم القرائي، ومهارات اللغة البراجماتية، وأوصى البحث باستخدام التعلم الموقفي عند التدريس للتلاميذ ذوي صعوبات القراءة، وضرورة الاهتمام بمهارات الفهم القرائي ومهارات اللغة البراجماتية.
The aim of this current research is to identify and recognize The effectiveness of a program which based on the situational learning in enhancing and devoloping reading comprehension skills and pragmatic language for elemantry reading difficulties students. The research experimental group consisted of 30 fourth grade reading difficulties students. The research materials and tools included a list of reading comprehension skills, list of pragmatic language aspects and diamentions and also the program based on the situational learning which included: the teacher's guide. the student's book and also included the following measure tools like: reading comprehension test, pragmatic observation criterion. The experimental strategy was used and applied in selecting the research group and the program appling. Using the semi-experimental one group through the pre and post applying the research tools. The program has been applied on research group students and applying the measurement tools on them also before and after. The results has been showed improvement in comprehension reading and pragmatic language skills for the students. The reaserch recommend applying the situational learning for learning difficulties students and the essential of paying attention to the reading comprehension and pragmatic language skills.
Keywords: البرامج التعليمية -- مهارات القراءة -- الفهم القرائي -- صعوبات القراءة -- التعليم الابتدائي